EFEKTIVITAS PERAN PENYULUH SWADAYA DALAM PEMBERDAYAAN PETANI DI PROVINSI JAWA BARAT - Yoyon Haryanto; Sumardjo Sumardjo; Siti Amanah; Prabowo Tjitropranoto (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2017)
The Role of progressive farmers for Farmer Empowerment in West Java. Farmer empowerment is increasingly marginalized by the reduced number of government extension workers in the village. It requires an alternative problem solving to narrow the poverty gap between cities and villages. Extension services providedly of progressive farmer are needed to help farmers. To find study analyze the role of progressive farmer in providing extension services and factor affecting the services contribute advantages to other farmers. A survey was conducted to gather data from 224 respondent who represent progressive farmers in four districts (Bogor, Karawang, Majalengka, and Sukabumi) West Java. Data processing using descriptive technique and regression analysis. The results show that the majority of progressive farmer have a high role as the facilitator of empowerment, motivator, technical assistant, environmental analyzer and marketing partner in farmer empowerment. It proves the effective role of progressive farmer in assisting farmers to obtain the information needed for their agribusiness activity. Farmers are able to cooperate with their community, able to choose innovations that appropriate to their specific location, or apply local innovations existed in their region. The role of progressive farmer  also has a positive effect on the effectiveness level of extension activities from farmers to farmers because they are able to facilitate and bridge the information for farmers from government research institutions and extension agencies.